Determinants of practice for providing decision coaching to facilitate informed values-based decision-making: protocol for a mixed-methods systematic review - Lindsey Sikora; Junqiang Zhao; Jeanette Finderup; Birte Berger-Höger; Dawn Stacey; Krystina B Lewis; Anke Steckelberg; Katherine Cherry; Janet Gunderson; Jana Kaden; Simone Kienlin; Anne C Rahn (BMJ Open, 2023)
Introduction Decision coaching is a non-directive approach to support patients to prepare for making health decisions. It is used to facilitate patients’ involvement in informed values-based decision-making and use of evidence-based health information. A recent systematic review revealed low certainty evidence for its effectiveness with and without evidence-based information. However, there may be opportunities to improve the study and use of decision coaching in clinical practice by systematically investigating its determinants of practice. We aim to conduct a systematic review to identify and synthesise the determinants of practice for providing decision coaching to facilitate patient involvement in decision-making from multiple perspectives that influence its use.Methods and analysis We will conduct a mixed-methods systematic review guided by the Cochrane’ Handbook of Systematic Reviews. We will include studies reporting determinants of practice influencing decision coaching with or without evidence-based patient information with adults making a health decision for themselves or a family member. Systematic literature searches will be conducted in Medline, EMBASE, Cochrane CENTRAL and PsycINFO via Ovid and CINAHL via EBSCO including quantitative, qualitative and mixed-methods study designs. Additionally, experts in the field will be contacted.Two reviewers will independently screen and extract data. We will synthesise determinants using deductive and inductive qualitative content analysis and a coding frame developed specifically for this review based on a taxonomy of barriers and enablers of shared decision-making mapped onto the major domains of the Consolidated Framework for Implementation Research. We will assess the quality of included studies using the Mixed Methods Appraisal Tool.Ethics and dissemination Ethical approval is not required as this systematic review involves only previously published literature. The results will be published in a peer-reviewed journal, presented at scientific conferences and disseminated to relevant consumer groups.PROSPERO registration number CRD42022338299.